2022
DOI: 10.1186/s10086-022-02025-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution characteristics of the dust emitted at different cutting speeds during MDF milling by image analysis

Abstract: Wood dust produced in medium-density fiberboard (MDF) processing is a major occupational hazard in wood industry and may damage processing equipment. In many wood processing factories, dust collecting systems need to be optimized for the distributional and morphological characteristics of dust in the workshop so that economical and efficient dust control can be achieved. In this study, weighting, image analysis and scanning electron microscopy (SEM) were applied to explore the effects of different cutting spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, absence of local exhaust ventilation (LEV), incorrect positioning of general air conditioners, use of compressed airlines and sweeping dust from furniture, clothes, work surfaces and processing tools were associated with higher dust levels. Recently, Cui et al [25] showed that higher mill cutter speeds were associated with an increase in dust levels.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, absence of local exhaust ventilation (LEV), incorrect positioning of general air conditioners, use of compressed airlines and sweeping dust from furniture, clothes, work surfaces and processing tools were associated with higher dust levels. Recently, Cui et al [25] showed that higher mill cutter speeds were associated with an increase in dust levels.…”
Section: Key Pointsmentioning
confidence: 99%
“…Engineering controls Proper use of dust extraction systems is regarded as the most important technical workplace control ] demonstrated that the use of main and auxiliary sawdust extraction connectors together ensured the highest reduction in wood dust exposures to 0.5 mg/m 3 during sawing activities. Baranski et al [49] and Cui et al [25] showed that correct design of the upper suction hood for dust extraction from circular saws, and the correct positioning of dust collecting hoods can improve the efficiency of dust removal. Furthermore, optimizing cutting parameters and the location of operators in relation to these machines can contribute to reducing the spatial distribution of MDF dust levels.…”
Section: Workplace Control Measures To Reduce Exposuresmentioning
confidence: 99%